Contradicción entre el principio de congruencia y el principio iuranovit curia en el sistema penal ecuatoriano. - Mármol, Cristian F. (2022)
Within the present study, it is necessary to verify the existence of a contradiction between the principle of congruence and the iura novit curia principle in the Ecuadorian penal system. Based on the analysis of concepts, doctrine, jurisprudence of International Courts about what the principle of consistency is and represents within the scope of criminal law, its application and its limits. Reference will also be made to the iura novit curia principle and its application at the time of resolving and making a decision by the person who dispenses justice (judges or courts). With the analysis of a sentence within a real case, we will verify if the application of the consistency principle was carried out correctly and based on the principle of fiscal accusation, that is, the accusation made by the prosecutor at the time of issuing his accusatory opinion. or if the guarantor exceeded the application of this optimization mandate and went further and applied the iura novit curia principle. It is essential to determine whether the application of the principle of congruence by the guarantor violates or does not basic guarantees of the right to defense of the procedural subjects within a criminal proceeding at the moment in which the application of this principle is contrary to the principle of fiscal accusation. As results and conclusions of this study, it is determined that there is a contradiction between the principle of consistency and the iura novit curia principle in criminal matters, but also in our current legislation there is a limit to the application of these principles